Pitiríase versicolor circinada: isolamento de Malassezia sympodialis - Relato de caso Pityriasis versicolor circinata: isolation of Malassezia sympodialis - Case report - Valéria Maria de Souza Framil; Márcia S.C. Melhem; Maria Walderez Szeszs; Elaine Cristina Corneta; Clarisse Zaitz (Anais Brasileiros de Dermatologia, 2010)
Os autores descrevem caso de pitiríase versicolor circinada, cujo agente etiológico isolado foi Malassezia sympodialis em uma mulher de 34 anos. O isolamento e identificação da Malassezia sympodialis foi em ágar Dixon modificado e o método molecular para confirmação da espécie foi PCR-RFLP (polymerase chain reaction and restriction fragment length polymorphism analysis). The authors report a case of pityriasis versicolor circinata whose isolated etiologic agent was Malassezia sympodialis in a 34-year-old woman. The isolation and identification of Malassezia sympodialis were accomplished with modified Dixon's agar, and the molecular method used to confirm the species was polymerase chain reaction and restriction fragment length polymorphism analysis (PCR-RFLP).